Indonesia Respons Pertumbuhan dan Hasil Tanaman Tebu (Saccharum officinarum L) Ratoon 2 Terhadap Kombinasi Zeolit dan Persentase Pupuk N: Tebu, Keprasan, Zeolit, Pupuk Nitrogen - Kusumastuti, Any; Indrawati, Wiwik; Aziz, Abdul; Zaqyah, Irene; Ayu Afifah, Dian; Apsoni, Rapi (Jurnal Penelitian Pertanian Terapan, 2024)
Sugarcane (Saccharum officinarum L.) is a plant that is cultivated to be processed into sugar. However, until now Indonesia has become a sugar importing country because the sugar industry is unable to meet the needs and demand for sugar which continues to increase as well as the high domestic selling price, so that it is necessary to import sugar to meet the demand for sugar in Indonesia. To overcome this is to apply Nitrogen fertilization on sugarcane combined with a companion material in the form of Zeolite. This study aims to obtain the growth and yield of ratoon 2 sugarcane plants by administering Zeolite and the proportion of N fertilizer as well as the interaction between the Zeolite and the proportion of N fertilizer. This study used a Randomized Block Design (RAK) Arranged in a split plot with two treatment factors repeated 3 times with 6 treatment combinations to obtain 18 experimental units. The main plot of Zeolite dosing with Z₀ is without zeolite and Z₁ is 700 kg.ha⁻¹ (equivalent to 0.8 kg.8m kairan⁻¹). Subplot dosage proportions of N fertilizer with P₁ is 100% urea (equivalent to 0.36 kg. 8m caustic⁻¹), P₂ is 80% urea (equivalent to 0.28 kg. 8m caustic⁻¹), and P₃ is 60% urea (equivalent to 0.21 kg. 8m caustic⁻¹). The results of this study indicate that the dose of Zeolite has an effect on all variable parameters of growth observations which include plant height, stem diameter, and number of internodes. As well as plant yields which include stem weight, stem length, brix value and yield. Application of [dose percentage of N fertilizer did not affect the growth and yield of sugarcane plants. There was no interaction between the Zeolite dosage and the proportion of N fertilizer doses on the growth and yield of sugarcane